1994
DOI: 10.1523/jneurosci.14-09-05399.1994
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neuron-specific tubulin defines a novel population in the proliferative layers of the developing telencephalon

Abstract: We have used a monoclonal antibody against the neuron-specific class III beta-tubulin (TuJ1; Lee et al., 1990b) to study the distribution and morphology of immature neurons in the proliferative ventricular and subventricular zones of the developing telencephalon. Mouse brains from embryonic day 12 (E12) to postnatal day 5 (P5) were fixed either with a non-cross-linking agent, HistoChoice, or with 4% paraformaldehyde, and processed for TuJ1 immunohistochemistry. TuJ1 immunoreactivity first appeared in the proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
302
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 439 publications
(327 citation statements)
references
References 65 publications
23
302
1
1
Order By: Relevance
“…This result was particularly interesting in light of previous studies showing that, in human tumor cells, TUBB3-incorporating microtubules have increased dynamic instability. 35,36 However, although the expression of Tubb3 has been described in some proliferating neuronal precursors of the telencephalon 37,38 and of the spinal cord, 39 this finding would be in apparent contrast with the strongly consolidated view that Tubb3 is a specific marker of postmitotic neurons. Therefore, we asked whether neuronal progenitors could express detectable amounts of Tubb3 protein during mitosis and whether this expression may correlate with neurogenesis.…”
Section: Resultsmentioning
confidence: 95%
“…This result was particularly interesting in light of previous studies showing that, in human tumor cells, TUBB3-incorporating microtubules have increased dynamic instability. 35,36 However, although the expression of Tubb3 has been described in some proliferating neuronal precursors of the telencephalon 37,38 and of the spinal cord, 39 this finding would be in apparent contrast with the strongly consolidated view that Tubb3 is a specific marker of postmitotic neurons. Therefore, we asked whether neuronal progenitors could express detectable amounts of Tubb3 protein during mitosis and whether this expression may correlate with neurogenesis.…”
Section: Resultsmentioning
confidence: 95%
“…The expression of Nolz-1 mRNA was decreased in the differentiated mantle zone. Double labeling showed that Nolz-1-positive cells coexpressed TuJ1, a marker of early differentiating neurons (27), in the SVZ (Fig. 4 I and J), suggesting that Nolz-1 was expressed in early differentiating neurons.…”
Section: Expression Of Nolz-1 Transcripts In Developing Rat Embryos Thementioning
confidence: 95%
“…At 10 days, ␤-III tubulin, an intermediate filament characteristic of mature neurons (Menezes and Luskin, 1994), was present in virtually all cells (Fig. 5B).…”
Section: Expression Of Neuroglial Genesmentioning
confidence: 95%